Co-operative and hierarchical binding of c-FLIP and caspase-8: a unified model defines how c-FLIP isoforms differentially control cell fate - Hughes, Michelle A.; Horn, Sebastian (Molecular cell, 2016)
The death-inducing signaling complex (DISC) initiates death receptor-induced apoptosis. DISC assembly and activation are controlled by c-FLIP isoforms, which function as pro-apoptotic (c-FLIPL only) or anti-apoptotic (c-FLIPL/c-FLIPS) regulators of procaspase-8 activation. Current models assume that c-FLIP directly competes with procaspase-8 for recruitment to FADD. Using a functional reconstituted DISC, structure-guided mutagenesis, and quantitative LC-MS/MS, we show that c-FLIPL/S binding to the DISC is instead a co-operative procaspase-8-dependent process. FADD initially recruits procaspase-8, which in turn recruits and heterodimerizes with c-FLIPL/S via a hierarchical binding mechanism. Procaspase-8 activation is regulated by the ratio of unbound c-FLIPL/S to procaspase-8, which determines composition of the procaspase-8:c-FLIPL/S heterodimer. Thus, procaspase-8:c-FLIPL exhibits localized enzymatic activity and is preferentially an activator, promoting DED-mediated procaspase-8 oligomer assembly, whereas procaspase-8:c-FLIPS lacks activity and potently blocks procaspase-8 activation. This co-operative hierarchical binding model explains the dual role of c-FLIPL and crucially defines how c-FLIP isoforms differentially control cell fate.